2015 IEEE International Conference on Teaching, Assessment, and Learning for Engineering (TALE) 2015
DOI: 10.1109/tale.2015.7386046
|View full text |Cite
|
Sign up to set email alerts
|

Coaching in computer-mediated communication at workplace

Abstract: Coaching is commonly defined as a developmental practice which requires the coach to provide an informal, ongoing form of goal-focused development aimed at improving and enhancing a person's performance. However, most of the previous human resource development studies examined coaching in face-to-face communication (FtFC), but fewer studies have looked at coaching in computer-mediated communication (CMC). This paper will focus on this untested concern which is how leaders appropriate the CMC to effectively coa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
0
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 40 publications
0
0
0
Order By: Relevance
“…Barbian (2002) suggests that "Trainers who are eager to remain important in the liaised world must connect the physical workspace with the virtual environment". Certainly, the trend of e-coaching is growing (Hui, 2015). Grant and Zackon (2004)'s research discovered that almost 64% of the study participants reported they used electronic methods of training at some point in time (Bucur, 2018).…”
Section: What Is E-coaching and What Is The Motivation Behind E-coach...mentioning
confidence: 99%
See 4 more Smart Citations
“…Barbian (2002) suggests that "Trainers who are eager to remain important in the liaised world must connect the physical workspace with the virtual environment". Certainly, the trend of e-coaching is growing (Hui, 2015). Grant and Zackon (2004)'s research discovered that almost 64% of the study participants reported they used electronic methods of training at some point in time (Bucur, 2018).…”
Section: What Is E-coaching and What Is The Motivation Behind E-coach...mentioning
confidence: 99%
“…E-coaching provides mechanisms for immediate and time-deferred connections, communications, and considerations (Bucur, 2018;Chang, 2009;Hubbard, 2015;Hui, 2015;Olszewski-Kubilius, 2013;Stein & Wanstreet, 2020). E-coaching can be used solely or as part of a hybrid learning project (Hamilton & Scandura, 2003;Headlam-Wells, Gosland, & Craig, 2006;Pulley, 2007).…”
Section: What Is E-coaching and What Is The Motivation Behind E-coach...mentioning
confidence: 99%
See 3 more Smart Citations